Explorando la actitud y expectativas en estudiantes de enseñanza primaria hacia el aprendizaje STEAM: un enfoque multidimensional en escuelas rurales en la insularidad de Chile - Kroff Trujillo, Francisco (2025)
This study examines the attitudes and expectations of primary school students towards STEAM learning in rural schools in Chile, emphasizing its role in fostering 21st-century skills. A mixed-methods design was employed, combining surveys and semi-structured interviews with 54 fifth- and sixth-grade students in a context characterized by technological limitations. The findings reveal positive perceptions of STEAM, with high levels of motivation and a preference for artistic and hands-on activities. The study concludes that promoting equity in access to STEAM education is crucial, as overcoming gender stereotypes and resource constraints is key to ensuring inclusive education that supports the academic and professional futures of students in rural settings.